Perceived Information Quality in Data Exchanges: Effects on Risk, Trust, and Intention to Use - Nicolaou, Andreas I.; McKnight, D. Harrison (Information Systems Research, 2006)
This study examines the role of information quality in the success of initial phase interorganizational (I-O) data exchanges. We propose perceived information quality (PIQ) as a factor of perceived risk and trusting beliefs, which will directly affect intention to use the exchange. The study also proposes that two important system design factors—control transparency and outcome feedback—will incrementally influence PIQ. An empirical test of the model demonstrated that PIQ predicts trusting beliefs and perceived risk, which mediate the effects of PIQ on intention to use the exchange. Thus, PIQ constitutes an important indirect factor influencing exchange adoption. Furthermore, control transparency had a significant influence on PIQ, while outcome feedback had no significant incremental effect over that of control transparency. The study contributes to the literature by demonstrating the important role of PIQ in I-O systems adoption and by showing that information cues available to a user during an initial exchange session can help build trusting beliefs and mitigate perceived exchange risk. For managers of I-O exchanges, the study implies that building into the system appropriate control transparency mechanisms can increase the likelihood of exchange success.